West of Center : Art and the Counterculture Experiment in America, 1965-1977 - Auther, Elissa; Lerner, Adam, 1966- (University of Minnesota Press ; Published in cooperation with the Museum of Contemporary Art Denver, 2012)
". In the heady and hallucinogenic days of the 1960s and '70s, a diverse range of artists and creative individuals based in the American West--from the Pacific coast to the Rocky Mountains and the Southwest--broke the barriers between art and lifestyle and embraced the new, hybrid sensibilities of the countercultural movement. Often created through radically collaborative artistic practices, such works as Paolo Soleri's earth homes, the hand-built architecture of the Drop City and Libre communes, Yolanda López's political posters, the multisensory movement workshops of Anna and Lawrence Hal.